Jingqianshu granules mitigates premenstrual depression by regulating orexin signaling - Dong, Ping; Dai, Weibo; Zhao, Tingting; Gong, Yuandong; Weng, Ning; Lv, Shimeng; Zhao, Yifan; Du, Chunyu; Ma, Yuexiang; Zhang, Zhen; He, Shuhua; Zheng, Feng; et al. (Frontiers in Pharmacology, 2024)
Premenstrual dysphoric disorder (PMDD), a severe form of premenstrual syndrome (PMS), is a serious health disorder that affects patient moods. It is caused by cyclic psychological symptoms and its pathogenesis is still unclear. Abnormalities in the basolateral amygdala (BLA) orexin system, which are important causes of the development of depressive mood, have not been reported in PMDD, so exploring its intrinsic mechanisms is meaningful for enriching the pathomechanisms of PMDD. This study developed a rat model of premenstrual depression, based on the forced swimming test, with a regular estrous cycle. The experiment consisted of two parts, in part 1, rats were divided into the control group, model group, model + Jingqianshu group, and model + fluoxetine group. The results showed that during the estrous cycle, rats exhibited depressive-like behavior during the nonreceptive phase in the forced swimming test, open field test, and elevated plus maze test, which disappeared during the receptive phase. Jingqianshu granules, a Chinese patent medicine for the treatment of PMS, reversed behavioral symptoms in model rats during the non-receptive phase. In addition, model rats had abnormal expression of orexin, toll-like receptors-4 (TLR4), nuclear factorkappa-B (NF-κB), tumor necrosis factor (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6), and treatment with Jingqianshu granules reversed all changes to physiological levels. In part 2, rats were divided into the control group, model group, and model+orexin-A group. Injections of orexin-A into the brain regions of rats in a premenstrual depression model inhibit microglia activation and decrease the expression levels of the mentioned inflammatory factors. In conclusion, the mechanisms of Jingqianshu granules for premenstrual depression may be related to the orexin system and neuroinflammation.